Evaluating the Revitalization of Medan’s Kesawan Area Through the Lens of The Finding Lost Space Theory - Nazri Fahmi; Abdi Sugiarto; Cut Nuraini (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research is an evaluative study of the old urban area of Kesawan in Medan City, which has been part of the city’s revitalization efforts initiated by the Medan City Government. Kesawan possesses strong historical and colonial architectural character but has undergone functional and visual degradation due to uncontrolled modern urban development. One of the key issues identified is the presence of inactive urban spaces, disconnected from the public realm and lacking social meaning—phenomena recognized in urban theory as lost space. This concept serves as the foundation for evaluating the effectiveness of the revitalization program implemented since 2021. The study employs a qualitative approach using a single-case study method, focusing on Kesawan as a complex urban space. Data were collected through field observations, in-depth interviews with five categories of informants (building owners, visitors, security personnel, street vendors, and architects), and visual documentation. The analysis adopts the theoretical framework of Finding Lost Space by Roger Trancik (1986), which comprises three main approaches: Figure-Ground Theory, Linkage Theory, and Place Theory. These were further elaborated into six evaluative indicators: connectivity, continuity and circulation, enclosure, accessibility, visual orientation, and the meaning and perception of space by the public. The findings indicate that revitalization has brought significant visual improvements and physical enhancements, particularly along the main corridor of Jalan Ahmad Yani I–VII. However, many secondary streets and non-priority areas still exhibit characteristics of lost space, such as disconnected pedestrian paths, underutilized voids, weak spatial integration, and limited social engagement. These conditions suggest that the revitalization outcomes remain uneven and predominantly cosmetic in certain areas. The study recommends integrating spatial and social approaches in future urban revitalization policies to ensure that public space functions can be restored holistically, sustainably, and contextually in line with local identity.